FRAGMEN TARI SUGRIWA SUBALI KARYA DIDIK BAMBANG WAHYUDI (TINJAUAN ESTETIK) - Annisa Ayu Cahyani; Maryono Maryono (Greget, 2020)
Research entitled Sugriwa Subali Dance Fragment by Didik Bambang Wahyudi (Aesthetic Review) is aim to uncover the meaning beauty of Sugriwa Subali Dance Fragment by describes and explains abaout: (1) the shape or sensation of Sugriwa Subali Dance Fragment which cover: theme, motion, expression, floor patterns, make-up, clothing, property and dance music/musical instruments, (2) to explain the concepts or ideas in the Sugriwa Subali Dance Fragment, (3) to explain the aestetic symbols in the Sugriwa Subali Dance Fragment, and (4)audience responses include: the responses of experts, dancers, and spectator. The four problems are examined with aestetic theory De Witt H Parker. In its application to analyze shapes as sensation expressed in the work using performance art theory according to Maryono. Analysis of consepts or idea in the work uses a pragmatic approach with Kreidler’s speech act theory. The research is qualitatively by collecting data or information through the stage of presentingdance work (re-production), literature study, interviews with selected speakers, and observation of the Sugriwa Subali Dance Fragment. The result was: the dance work is based on sensations, concepts or ideas, symbols, and the responses of experts, dancers, and spectator aestetically. Sugriwa Subali Dance Fragement is the masterpiece of the battle between Sugriwa and Subali fight over to Dewi Tara and the funcions as an aesthetic entertainment and as a symbol of strunggle in obtaining a happiness.Keywords: Fragment of Sugriwa Subali Dance, aesthetic.